(untitled) (LEARNing Landscapes, 2015)
In this interview, Judith McBride describes how she first became interested in teacher research as a graduate student and how a summer school course with influential educator Jack Whitehead propelled her through a "huge transformation" that changed the way she taught and the way she thought about teaching. She was involved in teacher research during her career as a high school teacher and was instrumental in guiding other teachers in action research and narrative inquiry. Now retired from teaching, she continues to contribute to this field in a variety of projects and shares her advice to teachers who wish to research their own practice.